Respon Pertumbuhan Dan Hasil Jagung Manis (Zea mays saccharata) Pengaruh Waktu Penyemprotan Herbisida Pada Jarak Tanam Yang Berbeda - Eko Hariyanto; Supandji Supandji; Tjatur Prijo Rahardjo; Nugraheni Hadiyanti (Universitas Kadiri, 2022)
Zea mays saccharata or sweet corn has become a leading horticultural commodity. It is not only limited to vegetables that are consumed normally but come with a variety of preparations. Therefore, there is a need for research on sweet corn productivity due to the interaction effect of herbicide spraying time treatment and plant spacing. In this study, sweet corn seed planting materials of TALENTA variety and selective herbicide PAG (Anti-Weed Package) were used with the active ingredients of Atras 600 sc and Aleron 60 sc. The research was carried out using the RAK environmental design (Randomized Block Design) with 3 replications and 2 treatment factors, namely 3 levels of spacing and herbicide spraying time which also consisted of three levels. Observations using destructive and non-destructive methods. By observing the variables of plant height, the number of leaves, stem diameter, leaf width, length of ear, the weight of ear, and diameter of the ear. The data obtained from the observational variables were processed by the F test using the ANOVA method. If there are treatments that are significantly different, a 5% Least Significant Difference test will be carried out. Planting distance J2: 70 x 30 cm and spraying herbicide PAG at P2:14 DAP was the best spacing and spraying time for sweet corn cultivation. Optimal spacing and proper spraying time can reduce the level of competition between cultivated plants and cultivated plants with weeds.